(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article reflects information about the emergence, early activities, location of schools of early music in the regions of Fergana, Andijan, Namangan. Information about the dynamics of the growth of the process of establishing music schools over the years has been cited and the rIneasons have been analyzed. At the same time, the functioning of music schools in certain periods as part of various ministries is covered on the basis of archival materials, scientific facts.